Intestinal microbiota dysbiosis in children with recurrent respiratory tract infections. (November 2019) - Li, Lei; Wang, Fang; Liu, Yanni; Gu, Feng
Abstract: Background: The impact of the gut microbiota on recurrent respiratory tract infection (RRTI) remains to be fully elucidated. Methods: To characterize the gut microbiota in patients with RRTI, fecal samples from 26 patients with RRTI and 23 healthy volunteers were profiled using the Illumina MiSeq platform. Beta diversity (Principal Component Analysis (PCA), Principal Co-ordinates Analysis (PCoA), Non-metric multidimensional scaling (NMDS)) analysis showed that the bacterial community structure segregated differently between the RRTI and control groups. Results: Results from alpha diversity analysis revealed lower microbiota diversity in samples from RRTI patients than in normal controls. Taxonomic analysis illustrated that the abundance of six phyla ( Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, Verrucomicrobia, Tenericutes ) and four genera ( Enterococcus, Faecalibacterium, Bifidobacterium, Eubacterium were significantly different between these two groups. In addition, Enterococcus (P < 0.001) was more enriched in the RRTI group, whereas the abundances of Eubacterium (P < 0.001), Faecalibacterium (0.01 < P < 0.05) and Bifidobacterium (0.01 < P < 0.05) were reduced in the RRTI group compared to those in the normal control group. The performance of the model was assessed using ROC analysis, and Enterococcus, Eubacterium and Bifidobacterium achieved AUC values of 0.860, 0.820, and 0.689, respectively. Conclusions: These results provide fundamental evidence in support of intestinal microbiota dysbiosis in children with RRTI. Highlights: Microbiota diversity lower in samples from RRTI patients compared with normal control. Six phyla were significantly different between RRTI patients and normal controls. Four genera were significantly different between RRTI patients and normal controls.